Metaheuristics for intelligent electrical networks - Héliodore, Frédéric; Nakib, Amir; Ismail, Boussaad; Ouchraa, Salma; Schmitt, Laurent (ISTE, Ltd., 2017)
The optimisation tools are ubiquitous in modelling and the use of electrical networks. Managing the complexity of these electrical networks leads to analyse and define new methodologies, able to combine performance and near-operational processing. Metaheuristics offer a range of solutions as efficient as they are innovative.
Includes bibliographical references and index. - Online resource; title from PDF title page (Ebsco, viewed August 29, 2017)
Keywords: Smart power grids; Réseaux électriques intelligents; TECHNOLOGY & ENGINEERING; Mechanical